Analysis Of Labor Qualifications Using The Resource Leveling Method On The Main Structure Work Of Multi-Story Buildings - Amelia Indah Faradilla; I Nyoman Dita Pahang Putra (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
Construction projects are related to infrastructure development in Indonesia, which is an important foundation for economic growth by supporting mobility, trade, and connectivity between regions. Infrastructure development also supports the utilization of labor resources in Indonesia. This research aims to analyze the availability of labor in a construction project. The Resource Leveling method is used to level the labor needs in the project. The results showed that there was an allocation of labor that exceeded the maximum daily availability before equalization. The initial allocation based on qualifications showed that the maximum number of workers consisted of 2 foremen, 1 head carpenter, 1 head ironworker, 1 head mason, 5 carpenters, 5 ironworkers, 1 mason, and 13 workers. After equalizing the workforce, the maximum number of workers required is 1 foreman, 1 head carpenter, 1 head ironworker, 1 head mason, 4 carpenters, 4 ironworkers, 1 mason, and 13 workers. This research emphasizes the importance of workforce equalization to avoid over-allocation and ensure efficiency in construction projects.